2010
DOI: 10.1038/sj.bjc.6606026
|View full text |Cite
|
Sign up to set email alerts
|

The HPV16 E6 binding protein Tip-1 interacts with ARHGEF16, which activates Cdc42

Abstract: Background:Guanidine exchange factor (GEF)-catalysed activation of Rho proteins such as Cdc42 has been shown to have a crucial role in cellular transformation, malignant progression and invasion. We have previously shown that the HPV16 E6 oncoprotein binds to the PDZ domain protein Tax-interacting-protein 1 (Tip-1) and we now report identification and functional analysis of a novel Tip-1 binding GEF.Methods:Yeast two-hybrid, in vitro pull-down, site-directed mutagenesis, semiquantitative PCR, co-immunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 35 publications
4
39
0
Order By: Relevance
“…Although more studies are needed to elucidate the mechanism(s), TIP-1 likely controls secretion of those angiogenic factors. Several TIP-1-interacting proteins, such as such as β-catenin [7], Rhotekin [9], and ARHGEF16 [12], are directly or indirectly involved in the activation of Rho GTPases for protein secretion [43; 44]. Roles of TIP-1 in the glioblastoma formation and growth and its proposed mechanisms of action were summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more studies are needed to elucidate the mechanism(s), TIP-1 likely controls secretion of those angiogenic factors. Several TIP-1-interacting proteins, such as such as β-catenin [7], Rhotekin [9], and ARHGEF16 [12], are directly or indirectly involved in the activation of Rho GTPases for protein secretion [43; 44]. Roles of TIP-1 in the glioblastoma formation and growth and its proposed mechanisms of action were summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TIP-1 involves in a wide spectrum of biological processes through selective protein interactions, such as beta-catenin [7], brain-specific angiogenesis inhibitor 2 [8], rhotekin [9], HPV16 E6 [10], HTLV-1 Tax [11], ARHGEF16 [12], potassium channel Kir2.3 [13], and glutaminase [14]. TIP-1 has been reported to regulate gastrulation movements during zebrafish embryo development [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, [14] Plexin D1 has been connected to Tip-1, which was established as an interactor of E6, which is the cervical cancer oncogene. [15] To further investigate the possible role of Plexin D1 in the cervical cancer progression, we decided to study the expression of this gene in various cervical cancer stages. Previous studies [16] used in situ hybridization to establish expression of Plexin D1 in solid malignancies; our study aimed to confirm the previous results.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore it is the target of two separate tumor viruses (HTLV1 and HPV16). It has also been very recently shown that Tip-1 interacts with HP1616 E6 and the guanidine exchange factor Gef16 to activate Cdec42 (Oliver et al, 2011). Taking these findings in conjunction with the previously reported roles of Tip-1 in both Rho and Wnt signaling, this clearly indicates that Tip-1 is an important "hub" protein.…”
Section: Discussionmentioning
confidence: 61%
“…It was first identified by its interaction with the Human T-cell Lymphotrophic Virus, type 1 Tax protein (Olalla et al, 2001) and Tip-1 has also been shown to interact with glutaminase L (Olalla et al, 2001), Rhotekin (Reynaud et al, 2000), β-catenin (Kanamori et al, 2003), Kir 2.3 (Alewine et al, 2006), HPV16 E6 (Hampson et al, 2004) and GEF16 (Oliver et al, 2011). Tip-1 protein was considered of particular interest because it has been reported to interact with two viral oncogenes (E6 and Tax) (Hampson et al, 2004;Rousset et al, 1998).…”
Section: Introductionmentioning
confidence: 98%